Protocol for ultrarapid immunostaining of frozen sections. - Richter, T (1999)
Rapid immunostaining of frozen sections within a tolerable time span would be very helpful for intraoperative diagnosis. A protocol was therefore established using the enhanced polymer one-step staining (EPOS) system (Dako) with antibodies against leucocyte common antigen (LCA), cytokeratin (CK), and anti-melanoma (MEL). Best results with reliable and specific immunostaining and a labelling intensity comparable to standard immunostaining protocols were achieved with fixation of samples in 100% acetone for 20 seconds (CK, LCA) or two minutes (MEL), followed by incubation of the primary antibody and development of the chromogen reaction with 3,3'diaminobenzidine (DAB) for three and five minutes at 37 degrees C, respectively. The total procedure takes only 12 minutes, thus enabling rapid immunostaining on intraoperative frozen sections. Apart from its use in tumour classification, this method is especially useful in detecting tumour cells in sentinel lymph nodes.